(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This thesis explores the reflection of the linguistic worldview (linguistic picture of the world) in English and Uzbek fairy tales through a comparative linguocultural analysis. The linguistic worldview is understood as a system of concepts, values, cultural stereotypes, and cognitive models embedded in language that shapes a nation’s perception of reality. The study reveals both universal archetypes common to world folklore — such as the triumph of good over evil, trials and tests, magic helpers, and enchanted objects — and culture specific elements rooted in historical, geographical, and religious contexts. English fairy tales often highlight individual heroism, personal destiny, adventure, and social mobility, reflecting Western European (Celtic, Anglo Saxon, medieval) values of freedom, courage, and individualism. In contrast, Uzbek fairy tales emphasize collective ethics, family harmony, communal justice, wisdom (donolik), patience, and harmony with nature, influenced by Turkic nomadic traditions, Islamic motifs, and Central Asian geography.